PENGEMBANGAN MEDIA LITERASI SAINS (MELISA) BERBASIS INTERAKTIF CONSTRUCT 2 PADA MATA PELAJARAN IPAS KELAS V DI SDN SINGOPADU TULANGAN - Hidayat, Arif Nur; Murni, Arie Widya (Jurnal Muassis Pendidikan Dasar, 2024)
This research discusses the development of interactive science literacy media (Melisa) based on Construct 2 in class V science subjects at SDN Singopadu. This type of research uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. This research aims to develop and measure the effectiveness of interactive scientific literacy media (Melisa) based on Construct 2. The media developed was validated by 2 validators. The results of the Melisa feasibility test research were based on the assessment: 1) The material expert validator obtained a percentage of 87.5% in the "Very Feasible" category. 2) Media expert validators got a percentage of 91.6% in the "Very Eligible" category. Thus, Melisa is declared suitable to be applied to students. The sample for this research was class V at SDN Singopadu, totaling 20 students. Data from student observations obtained a percentage of 80% and teacher observation results of 97% were in the "Very good" category. Data on learning outcomes before implementing the media was 60% and after implementing the media was 86.5%. The results show that student learning outcomes have increased and are in the "Very high" category. In addition, the competency aspect of scientific literacy in the indicator of identifying scientific issues was 93%, reaching the "Very High" classification, the indicator for explaining phenomena was 85%, reaching the "Very High" classification, and the indicator using scientific evidence was 80%, reaching the "Very High" classification. . This shows that scientific literacy media (Melisa) can train students' scientific literacy skills.